Geographic patterns and dimensions of poverty in the Indian Himalayan region - Golam Rasul; Apsara Karki Nepal (Heliyon)
Despite India's progress in reducing national poverty rates, pockets of severe poverty persist in the mountainous states comprising the Indian Himalayan Region (IHR). This paper examines the geographic patterns and dynamics of consumption as well as multidimensional poverty in the IHR, drawing insights from nationally representative household surveys. It explores the multifaceted factors influencing poverty, including geography, accessibility, social structures, economic activities, and environmental conditions. There is a significant variation in the incidence of consumption poverty across the IHR. While some states exhibit poverty rates lower than the national average, others, such as Assam, Arunachal Pradesh, and Manipur, record higher rates, emphasizing the need for tailored poverty alleviation strategies. Multidimensional poverty in the IHR slightly exceeds the national average, with deprivations spread across various dimensions, including health, education, living standards, economic opportunities, and inaccessibility. Both types of poverty are highly correlated with larger household size and dependency ratio, and schedule caste/tribes. The important factors that could help reduce poverty appear to be education, access to clean energy including electricity, better sanitation services, and access to mobile phone services. To address poverty effectively in the IHR, comprehensive strategies are essential, including the development of farm and non-farm sectors, the provision of essential services, and targeted interventions tailored to local contexts. The paper underscores the importance of recognizing the unique challenges faced by mountainous regions and calls for region-specific policy interventions to achieve sustainable poverty reduction.